Insect exhibition as a tool to promote biodiversity conservation among children - Farah Hani Mohd Ma`in,; Siti Fatimah Sabran,; Norradihah Ismail,; Maryati Mohamed,; Nur Bahiyah Abdul Wahab,; Arney Sapaat, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Strong understanding of biodiversity instilled in the early ages is critical to initiate the actions and sense of responsibility towards biodiversity conservation. However, poor effort in mainstreaming biodiversity could lead to lack of awareness and understanding on biodiversity among society, thus restricting effective conservation effort. Therefore, in this study, biodiversity conservation education was pursued using insects to promote awareness. This study aimed to gauge the level of biodiversity understanding and knowledge among primary school students before and after experiencing insect exhibition. This study involved two parts; insect exhibition (development of insect collection and posters) and surveys (using pre and post questionnaires). A total of 136 students of age 10 from four primary schools in Batu Pahat district, Johor, Malaysia participated in the exhibition. The results showed that the level of understanding on biodiversity’s concept and function among the students was poor before experiencing the exhibition while 80.15% of their understanding has increased after the exhibition. In conclusion, the use of insect collection with interactive display and activities during the exhibition could attract students and improve their learning and understanding on biodiversity conservation.